(untitled) (Health Renaissance, 2014)
Pseudopelade of Brocq is a clinical syndrome comprising of scarring alopecia and fibrosis in which distinct pathological features are absent. It is not a specific disease, rather a pattern of cicatricial alopecia. However, if a definitive diagnosis of DLE (discoid lupus erythematosus), LPP (Lichen planopilaris) or any other condition can be made on the basis of clinical, histopathological or immunofluorescent features, then this term cannot be used. Here we report the case of a 20 year old young male who presented to us with complaints of loss of scalp hair for 2 years which were associated with mild itching. The condition is as such rare in prevalence and hence we report the same in view of its unique presentation. DOI: http://dx.doi.org/10.3126/hren.v11i3.9652 Health Renaissance 2013;11(3):273-275